Peran Sejarah Lokal dalam Meningkatkan Literasi Sosial Mahasiswa Universitas Muhammadiyah Enrekang - Natsir, Mohammad; Chabir Galib, Andi Ahmad; Syawal, Syawal (Prodi Perpustakaan dan Sains Informasi, 2025)
This study aims to examine the role of local history in enhancing the social literacy of students at Universitas Muhammadiyah Enrekang. Local history is viewed as a rich learning resource containing social, cultural, and moral values that can strengthen students’ understanding of the social realities in their environment. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observations, and document analysis involving students engaged in learning activities and student programs based on local history. The findings show that student involvement in learning local history fosters the development of empathy, social awareness, and participatory attitudes in community life. Narratives of local history that reflect values such as mutual cooperation, solidarity, and collective struggle contribute to shaping students’ social literacy in a more contextual and reflective manner. This study recommends integrating local history into the curriculum and strengthening partnerships between universities and local communities as a strategy for developing students’ character education and social literacy.